2004
DOI: 10.1002/nur.20042
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, self‐efficacy, and perceived exertion among adolescents

Abstract: The relationship of self-efficacy, a sense of confidence in personal physical activity (PA) skills, to perceived exertion during activity was explored among 168 African American and European American boys and girls between 9 and 17 years of age. Participants walked/ran on a treadmill at a speed equivalent to 60% of their peak VO2 for 20 minutes and provided ratings of exertion every 4 minutes. Pre-activity self-efficacy predicted perceived exertion for boys only. Girls were lower than boys in pre-activity self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
8
47
0
6
Order By: Relevance
“…The lack of a reprioritisation was unexpected given the large body of adolescent development literature that reports considerable changes in many areas related to QoL, such as family and peer relationships [41], physical self-perceptions [22,42] and life goals [9]. However, the findings are consistent with prior research, not directly assessing RS, but which has reported similar stability in the relative importance of domains.…”
Section: Discussionsupporting
confidence: 85%
“…The lack of a reprioritisation was unexpected given the large body of adolescent development literature that reports considerable changes in many areas related to QoL, such as family and peer relationships [41], physical self-perceptions [22,42] and life goals [9]. However, the findings are consistent with prior research, not directly assessing RS, but which has reported similar stability in the relative importance of domains.…”
Section: Discussionsupporting
confidence: 85%
“…The female children's lower level of aerobic fitness may have resulted in higher perceptions of exertion at any given time point during the shuttle run. In a study of 9-to 17-yr-old children performing incremental treadmill exercise, Robbins et al (21) noted that females tended to report greater exertion than males during each of the study periods. They attributed this response to lower fitness levels in the females (21).…”
Section: Discussionmentioning
confidence: 96%
“…In a study of 9-to 17-yr-old children performing incremental treadmill exercise, Robbins et al (21) noted that females tended to report greater exertion than males during each of the study periods. They attributed this response to lower fitness levels in the females (21). Interestingly, Robertson also noted that when adult males and females performed at the same submaximal exercise intensity, RPE-O was higher for the individuals who had the lower aerobic fitness level (23).…”
Section: Discussionmentioning
confidence: 96%
“…A falta de movimentação nas aulas de educação física é um fator comumente relatado por alunos como sendo uma das causas da não participação 40 . Um fato que poderia justificar a realização de au-las com menor movimentação é que a aula com muita movimentação resultaria em aumento da intensidade da atividade, gerando percepções de desconforto durante a realização, o que ocasionaria a desistência da tarefa realizada, como já descrito em jovens 41 . Isso não foi confirmado pelos achados do presente estudo, haja vista que não foram encontradas associações entre se sentir cansado após as aulas de educação física e participação nas mesmas.…”
Section: Métodosunclassified